Chemical responses of small boreal lakes to atmospheric and catchment drivers over four decades - Arvola, Lauri; Rask, Martti; Huotari, Jussi; Tulonen, Tiina; Kahilainen, Kimmo K.; Ruuhijärvi, Jukka; Lindberg, Henrik; Viitala, Risto; Blanchet, Clarisse; Arzel, Celine; Nummi, Petri; Salonen, Kalevi (Elsevier BV, 2025)
During the last few decades organic matter concentrations and water colour values have increased in a large number of lakes and rivers in Eurasia and North America. The upward shift in colour, often called water browning, and shortage of mobile cations have been linked to the recovery of catchments and lakes from acid deposition and increased precipitation. Here, long-term water chemistry responses of 33 boreal forest lakes to atmospheric and catchment scale drivers were studied in a small drainage basin in southern Finland. The longest data series cover four decades starting in 1979, and thus include the period of highest acid deposition in the middle of the 1980s and its dramatic decline during the next decade. The water quality data was taken during the autumn mixing, and in this long-term data set water colour increased significantly in 23 lakes, and the most uniform increase took place in the 1990s. In lakes fed predominantly by surface-waters, colour and iron have largely behaved in parallel, both responding to the variation in hydrology with higher concentrations after wet summers. Seepage lakes, in contrast, have responded to rainy periods less noticeably. In accordance with previous studies, the results indicate that most recent changes in colour have been hydrologically driven and are lake-specific rather than consistent among the lakes. In the long-term, the base cation concentrations have declined in most lakes, resulting in electrolyte dilution, loss of alkalinity, and decreased pH. In the uppermost headwater surface water lakes, iron concentrations showed an increasing trend since 1990, but in this century the trends have been less clear. Overall, the results suggest that 25 years after the most rapid reduction in atmospheric deposition, the studied lakes are still undergoing chemical recovery. Forestry practices and beavers may have impacted on many lakes as well, complicating interpretation of the chemistry patterns caused by changes in deposition and hydrological conditions, and lake-specific characteristics.